Accountability of Village Financial Management in Thematic Tourism Villages - Yuni Lestari Br Sitepu; Elisabet Siahaan; Ance Marintan D. Sitohang (International Journal of Business and Applied Economics, 2023)
This study aims to determine the influence of the role of village officials, village apparatus competence, community participation, and information technology on village financial management accountability. The method for determining the sample is proportional stratified random sampling and data collection using a questionnaire. This study shows that community participation and information technology have a significant effect on village financial management accountability. This study shows that the better community participation and information technology are, the better the accountability of village financial management. Meanwhile, the role and  competence of village officials do not affect the accountability of village financial management. The competence of village officials in this study is still inadequate and still requires regular assistance and training for accountability in village financial management.